Does Active Labour Market Policy Reduce Unemployment when Search is Endogenous? - Trine Filges; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2000)
We analyse the effects active labour market programmes (ALMPs) have on unemployment in a union wage-setting framework when search is endogenous. We assume that a union president, elected by majority voting determines the wage. We analyse the case where ALMPs increase match efficiency of the marginalized workers, and show that ALMPs may increase unemployment.
hdl:10398/7515
Keywords: J41; J64; J68; 330; Endogenous Search; Active Labour Market Policy; Unemployment